Positive correlation between Merkel cell polyomavirus viral load and capsid-specific antibody titer - Pastrana, Diana V. (Springer-Verlag, 2011)
Merkel cell polyomavirus (MCPyV or MCV) is the first polyomavirus to be clearly implicated as a causal agent underlying a human cancer, Merkel cell carcinoma (MCC). Infection with MCPyV is common in the general population, and a majority of adults shed MCPyV from the surface of their skin. In this study, we quantitated MCPyV DNA in skin swab specimens from healthy volunteers sampled at different anatomical sites over time periods ranging from 3 months to 4 years. The volunteers were also tested using a serological assay that detects antibodies specific for the MCPyV virion. There was a positive correlation between MCPyV virion-specific antibody titers and viral load at all anatomical sites tested (dorsal portion of the hands, forehead, and buttocks) (Spearman’s r 0.644, P < 0.0001). The study results are consistent with previous findings suggesting that the skin is primary site of chronic MCPyV infection in healthy adults and suggest that the magnitude of an individual’s seroresponsiveness against the MCPyV virion generally reflects the overall MCPyV DNA load across wide areas of the skin. In light of previous reports indicating a correlation between MCC and strong MCPyV-specific seroresponsiveness, this model suggests that poorly controlled chronic MCPyV infection might be a risk factor in the development of MCC. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00430-011-0200-7) contains supplementary material, which is available to authorized users.